Impact of the "Tobacco control law" on exposure to environmental tobacco smoke in Spain - Zorrilla Belén; Velázquez Luis; Díez-Gañán Lucía; Estrada Carmen; Mata Nelva; Galán Iñaki; Gandarillas Ana; Ortiz Honorato (BMC, 2007)
Abstract Background The initial evaluations of the introduction of legislation that regulates smoking in enclosed public places in European countries, describe an important effect in the control of exposure to environmental tobacco smoke. However, the evidence is still limited. The objective of this study is to estimate the short-term effects of the comprehensive "Tobacco control law" introduced in Spain on January 2006, which includes a total ban of smoking in workplaces and a partial limitation of smoking in bars and restaurants. Methods Cross-sectional, population-based study. The self-reported exposure to environmental tobacco smoke at home, at work, in bars and restaurants of the population aged 18 to 64 years in the Madrid Region during a period prior to the law (October and November 2005; n = 1750) was compared to that of the period immediately after the law came into force (January-July 2006; n = 1252). Adjusted odds ratios (OR) were calculated using logistic regression models. Results Passive exposure to tobacco smoke at home has hardly changed. However, at indoor workplaces there has been a considerable reduction: after the law came into force the OR for daily exposure > 0-3 hours versus non-exposure was 0.11 (95% CI: 0.07 to 0.17) and for more than 3 hours, 0.12 (95% CI: 0.09 to 0.18). For fairly high exposure in bars and restaurants versus non-exposure, the OR in the former was 0.30 (95% CI: 0.20 to 0.44) and in the latter was 0.24 (95% CI: 0.18 to 0.32); for very high exposure versus non-exposure they were 0.16 (95% CI: 0.10 to 0.24) and 0.11 (95% CI: 0.07 to 0.19), respectively. These results were similar for the smoking and non-smoking populations. Conclusion A considerable reduction in exposure to environmental tobacco smoke in the workplace and, to a lesser extent, in bars and restaurants, is related to the implementation of the "Tobacco control law". Although only initial figures, these results already demonstrate the effectiveness of strategies that establish control measures to guarantee smoke-free places.